Recurrent oral metastatic lesion of renal cell carcinoma - A case report - A Kizaekka; P Chengot; CJ Mannion (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2019)
Metastatic lesions to the oral cavity are extremely rare, accounting for approximately 1% of all malignant oral tumours [1]. Although an uncommon tumour, Renal Cell Carcinoma (RCC) is the most common type of renal tumour presenting in adults, originating from the lining of the proximal convoluted tubule. It is responsible for approximately 90%-95% of all cases in kidney cancer [1]. It is known to metastasise 20% to 25% most frequently to the brain and liver. Renal Cell Carcinoma can also metastasise to the oral cavity, although rarely (around 1%).